2021
DOI: 10.1177/07435584211064566
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of a Reconceptualized Definition and Measure of Adolescent Risk Behavior: Adolescent Viewpoints

Abstract: The goal of this project was to substantiate a more positive conceptualization of adolescent risk behavior and to compare adolescent viewpoints of risk behavior to the items on the Prosocial and Health Adolescent Risk Behavior Scale (PHARBS). A total of 57 high school students participated in the research. Researchers recruited students from an Advanced Placement (AP) Psychology course at a large Midwestern high school. The high school serves approximately 1,750 students in grades 9 through 12. The university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…However, adolescents may not view risk behavior from the same perspective as adults (Defoe and Romer, 2022). Namely, as noted above, Skaar (2021) found that educational risk behaviors (e.g., taking challenging classes) were the most mentioned by youth as risk behaviors, followed by "drug and alcohol use" and "trying something new. " Related to this, Duell and Steinberg, (2021) recently presented an approach that focuses on adaptive forms of risk taking, such as developing a new skill, that need to be encouraged despite the prospect of challenges that such learning may require.…”
Section: More Recent Positive Risk-taking Researchmentioning
confidence: 97%
See 4 more Smart Citations
“…However, adolescents may not view risk behavior from the same perspective as adults (Defoe and Romer, 2022). Namely, as noted above, Skaar (2021) found that educational risk behaviors (e.g., taking challenging classes) were the most mentioned by youth as risk behaviors, followed by "drug and alcohol use" and "trying something new. " Related to this, Duell and Steinberg, (2021) recently presented an approach that focuses on adaptive forms of risk taking, such as developing a new skill, that need to be encouraged despite the prospect of challenges that such learning may require.…”
Section: More Recent Positive Risk-taking Researchmentioning
confidence: 97%
“…In a unique recent qualitative study (N = 57; 77% female; >90% European American), adolescents were asked the following question "What behaviors come to mind when I say "risk behavior?" (Skaar, 2021).…”
Section: New Directions Toward Risk-takingmentioning
confidence: 99%
See 3 more Smart Citations